The Agricultural Commodity Trading Design through E-Commerce Channel Affecting the Success and Development Guidelines for the Model of Agricultural Commodity Trading Support in the Eastern Region: A Case Study of Durian in Rayong and Chanthaburi Province - Tanrattanakul, Atip; Kaeosawan, Chanisara; Wiroonratch, Sirinya (Suan Dusit Graduate School Academic Journal, 2022)
The objectives of this research were to study the problems, obstacles and guidelines for the development model to support the trading of agricultural products through the e-commerce system of durian farmers in the eastern region and to study the relationship between the design of agricultural products trading through e-commerce channels and the success of agricultural commodities trading through e-commerce channels and the development model to support trading in agricultural commodities in the Eastern region. The mixed-method research method consisted of qualitative research by conducting in-depth interviews with 19 government and private stakeholders, together with quantitative research using 400 questionnaires to collect data with the representatives of durian farmers in Rayong and Chanthaburi provinces. In addition, the group discussion with 8 experts was also implemented. The results showed that problems and obstacles for the development of agricultural commodity trading support in the eastern region could be divided into 4 issues including problems in quality and quantity of durian, government support, logistics system and distribution channel. The development guidelines for the trading support model of agricultural products in the eastern region consisted of 4 aspects: quality and quantity of durian, government support, logistics system and distribution channels. Regarding the relationship between the factors, the design factors of agricultural products trading through e-commerce channels that affected the success of agricultural products trading through electronic commerce channels included product sellers, service website area, e-commerce system, freight operator and buyer. Factors of the success of agricultural commodity trading through e-commerce channels that affected the development of a support model for agricultural commodity trading in the eastern region included export customs laws and regulations, import customs laws, trade barriers, competitors, and expertise of farmers.